2015
DOI: 10.1007/s11356-015-5359-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of personal care products and hormones in leachate and groundwater from Polish MSW landfills by ultrasound-assisted emulsification microextraction and GC-MS

Abstract: Determination of the endocrine disrupting compounds (EDCs) in leachate and groundwater samples from the landfill sites is very important because of the proven harmful effects of these compounds on human and animal organisms. A method combining ultrasound-assisted emulsification microextraction (USAEME) and gas chromatography–mass spectrometry (GC-MS) was developed for simultaneous determination of seven personal care products (PCPs): methylparaben (MP), ethylparaben (EP), propylparaben (PP), buthylparaben (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…In the opinion of Kanownik and Policht-Latawiec (2016), such a state is characteristic of old landfills. In addition, the neutral reaction in the tested waters in the area of the landfill was also demonstrated by Kapelewska et al (2016). The reaction of the tested leachate was also close to neutral.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the opinion of Kanownik and Policht-Latawiec (2016), such a state is characteristic of old landfills. In addition, the neutral reaction in the tested waters in the area of the landfill was also demonstrated by Kapelewska et al (2016). The reaction of the tested leachate was also close to neutral.…”
Section: Discussionsupporting
confidence: 68%
“…The PAHs originate mainly from anthropogenic processes, in particular from incomplete combustion of organic fuels, and are widely distributed in the environment (Malakahmada et al 2016). Some researchers have shown that organic compounds can easily penetrate water or soil if the isolation between deposited waste and soil is insufficient (Kapelewska et al 2016; Nomngongo et al 2012). The degree of contamination of aquifers depends on the speed of transport and storage conditions at the place where they penetrate the soil structure (Vasanthi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of Cr +6 , Cd, Cu, Pb and Hg remained at a low level, similar to the neutral reaction. Kapelewska et al ( 2016 ) observed a neutral water reaction in the area of the landfill. However, it should be noted that in the case of Cd at an average concentration of 0.001 mg/L below the landfill, there was a high correlation in the relationship between groundwater and leachate and two types of water below the landfill.…”
Section: Discussionmentioning
confidence: 99%
“…Despite photodegradation and generation of radicals, OCFs cause other drawbacks for human health. For example, AVOB promotes obesogenic phenotypes in normal human epidermal keratinocytes (NHEKs), increasing the gene transcription of peroxisome proliferator-activated receptor γ (PPARγ) and fatty acid-binding protein [ 24 ], and affecting diabetes [ 25 ] with disruptive endocrine effects [ 26 ]. The toxic effect of some of the most representative OCFs are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%